In vitro and in vivo three-dimensional velocity vector measurement by three-beam spectral-domain Doppler optical coherence tomography - Trasischker, Wolfgang; Werkmeister, René M; Zotter, Stefan; Baumann, Bernhard; Torzicky, Teresa; Pircher, Michael; Hitzenberger, Christoph K (Journal of biomedical optics, 2013)
We developed a three-beam Doppler optical coherence tomography (OCT) system that enables measurement of the velocity vector of moving particles in three-dimensions (3-D). The spatial orientation as well as the magnitude of motion can be determined without prior knowledge of the geometry of motion. The system combines three spectral-domain OCT interferometers whose sample beams are focused at the sample by a common focusing lens at three different angles. This provides three spatially independent velocity components simultaneously from which the velocity vector can be reconstructed. We demonstrate the system in a simple test object (rotating disc), a flow phantom, and for blood flow measurements in the retina of a healthy human subject. Measurements of blood flow at a venous bifurcation achieve a good agreement between in- and outflow and demonstrate the reliability of the method.